The Disk Substructures at High Angular Resolution Project (DSHARP): VII. The planet-disk interactions interpretation - Zhang, Shangjia; Dullemond, Cornelis (Arxiv, 2018)
The Disk Substructures at High Angular Resolution Project (DSHARP) provides a large sample of protoplanetary disks having substructures which could be induced by young forming planets. To explore the properties of planets that may be responsible for these substructures, we systematically carry out a grid of 2-D hydrodynamical simulations including both gas and dust components. We present the resulting gas structures, including the relationship between the planet mass and 1) the gaseous gap depth/width, and 2) the sub/super-Keplerian motion across the gap. We then compute dust continuum intensity maps at the frequency of the DSHARP observations. We provide the relationship between the planet mass and 1) the depth/width of the gaps at millimeter intensity maps, 2) the gap edge ellipticity and asymmetry, and 3) the position of secondary gaps induced by the planet. With these relationships, we lay out the procedure to constrain the planet mass using gap properties, and study the potential planets in the DSHARP disks. We highlight the excellent agreement between observations and simulations for AS 209 and the detectability of the young Solar System analog. Finally, under the assumption that the detected gaps are induced by young planets, we characterize the young planet population in the planet mass-semimajor axis diagram. We find that the occurrence rate for $>$ 5 $M_J$ planets beyond 5-10 au is consistent with direct imaging constraints. Disk substructures allow us probe a wide-orbit planet population (Neptune to Jupiter mass planets beyond 10 au) that is not accessible to other planet searching techniques.
Gesehen am 19.08.2020